2012
DOI: 10.1128/jcm.00885-12
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive Hybridization Yields a Silver Resistance Determinant Unique to Nosocomial Pathogens in the Enterobacter cloacae Complex

Abstract: The heterogeneity and the increasing clinical importance of the Enterobacter cloacae complex have often been discussed. However, little is known about molecular factors causing pathogenicity within this nomenspecies. Here, we analyzed the genetic differences between an avirulent plant isolate and a pathogenic strain causing an outbreak with septicemia in three patients. We identified an IncHI-2 plasmid as a major difference between these two strains. Besides resistance to several antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The K. pneumoniae outbreak in Uppsala was also caused by a global clone, ST16 (12), which in recent years has been associated with several clinically important carbapenemases (45). Interestingly, it has been suggested that resistance to silver ions represents a potent fitness factor in members of the Enterobacter cloacae complex (46).…”
Section: Discussionmentioning
confidence: 99%
“…The K. pneumoniae outbreak in Uppsala was also caused by a global clone, ST16 (12), which in recent years has been associated with several clinically important carbapenemases (45). Interestingly, it has been suggested that resistance to silver ions represents a potent fitness factor in members of the Enterobacter cloacae complex (46).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the sil determinant has been associated with pathogenicity in the Enterobacter cloacae complex, where the presence of the genes conferring silver resistance was increased in isolates from hospital settings vs. strains associated with plants (Kremer and Hoffmann 2012). Although identification of the pco genes was not part of that study, their presence within the isolates harboring the full sil determinant is very likely based on the high rate of co-representation (Mourão et al 2015) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Homologues of the sil system have been detected using silspecific primers in IncH1-2 group plasmids from Gramnegative bacteria (Gupta et al, 2001), in oral bacteria (Davis et al, 2005), in nosocomial isolates of Enterobacter cloacae (Kremer & Hoffmann, 2012), a silver-resistant Enterobacter cloacae leg ulcer isolate (Sütterlin et al, 2012), some Gram-negative bacteria isolated from wounds ) and, surprisingly, in S. aureus (Loh et al, 2009). There are also some reports of silver-resistant pathogens which carry the sil genes that were isolated from burns units and even from the silver-containing burns creams (Pirnay et al, 2003).…”
Section: Silver Tolerance and Resistancementioning
confidence: 99%